IMPLEMENTING STRATEGIES OF DRILL AND ASSIGNMENT TO IMPROVING PROBLEM SOLVING ABILITY - Anwar Ardani; Dian Purwaningsih (Universitas Majalengka, 2021)
This research is based on the ability of students in which students have not been able to formulate a null hypothesis and an alternative hypothesis that is appropriate to the question or problem being asked. The purpose of this study was to determine whether or not there is an increase in student problem solving abilities from before being given the drill strategy and assignment treatment to after being given the drill strategy and assignment treatment. This research is a quasi-experimental design with one group pretest-posttest design. The population in this study were all elementary school teacher education students who took the education statistics course in the odd semester of the 2019/2020 school year. The sampling technique in this study used simple random sampling. The research was conducted on 30 PGSD students who took educational statistics courses. The data collection technique used the test method. The data analysis in this research used paired T test. The results showed that there was an increase in students' problem solving abilities from before being given the drill and assignment strategy treatment to after being given the drill and assignment giving strategy treatment